Upaya Meningkatkan Keaktifan Belajar Matematika: Implementasi Media Interaktif Wordwall Pada Siswa Kelas IV B MIN 3 Malang - Tri Wulandari, Aida Olivia Desy (Maliki Interdisciplinary Journal, 2025)
This article discusses efforts to increase mathematics learning engagement through the use of interactive media Wordwall for grade IV B students at MIN 3 Malang. Wordwall is a digital learning platform that provides various types of educational games that can foster student interest, motivation, and engagement in the learning process. The use of this media has been proven to create a more enjoyable, interactive, and competitive learning atmosphere. In addition, Wordwall media can also encourage students to be more active in answering questions, discussing, and expressing opinions. This article emphasizes that the success of Wordwall is not only determined by the media itself, but also by the teacher's strategy in managing the class and facilitating active student participation. Thus, Wordwall can be a relevant alternative learning media to improve the quality of mathematics learning in elementary schoolsThis article discusses efforts to increase mathematics learning engagement through the use of interactive media Wordwall for grade IV B students at MIN 3 Malang. Wordwall is a digital learning platform that provides various types of educational games that can foster student interest, motivation, and engagement in the learning process. The use of this media has been proven to create a more enjoyable, interactive, and competitive learning atmosphere. In addition, Wordwall media can also encourage students to be more active in answering questions, discussing, and expressing opinions. This article emphasizes that the success of Wordwall is not only determined by the media itself, but also by the teacher's strategy in managing the class and facilitating active student participation. Thus, Wordwall can be a relevant alternative learning media to improve the quality of mathematics learning in elementary schools.